WORK ACTIVITY IS THE MAIN FACTOR IN SOCIALIZING A PERSON. (Universal International Scientific Journal, 2026)
This article discusses the quality of women's work and quality of life in modern socio-economic conditions, the need to ensure their socio-psychological balance by improving the quality of women's work lives, labor productivity, professional activity and innovative potential, the individual's attitude to work and motivation, work motivation, social recognition, and the work team environment and support for women in the family.
Keywords: women's work, work activity, quality of life, attention, memory, logical thinking, combination of social roles